(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the extent to which student teachers practice basic science skills as a whole in the science education course, and in each basic skill separately, and to identify the differences in the extent to which they practice basic science skills according to the variables (sex and cumulative average).